Mapping Stakeholders in the Development of Eco-Cities: Insights from Nepal and Indonesia - Rana, Shreema; Aadisukma, Dana (Kathmandu University Journal of Science, Engineering and Technology, 2024)
Urban areas are dynamic and intricate, encompassing various social, economic, ecological, and cultural aspects. It's crucial to employ effective approaches and management methods to achieve sustainable urban development. Stakeholder analysis is pivotal in understanding their roles and responsibilities in this process. By analyzing potential stakeholders and their responsibilities, enhances achieving development goals. This paper uses ‘solid waste bank’ and ‘socio-cultural water management approach’ case of Surabaya, Indonesia and Lalitpur, Nepal respectively. The challenges stakeholders face when implementing have been studied and mapped. Additionally, the significance of stakeholders in implementing development plans and policies has been reviewed through relevant journals and reports, considering the current cases of solid waste management and water management only. The mapping of stakeholders’ problems and prospects revealed that none of the stakeholders had low influence and low importance in both Nepal and Indonesia. This finding suggests that further studies could explore other relevant aspects of the stakeholder dynamics that could contribute to developing eco-city in both the countries. Also mapping, synthesizing both situation and stakeholder of other practices, and upgrading the practices as well may help achieve eco-city, which is unique, inclusive and has the contextual flavors.